Avulsion fractures of the ischial tuberosity in the pediatric athlete: a systematic review and return to sport analysis. Issue 5 (9th June 2022) - Vadhera, Amar S.; Knapik, Derrick M.; Gursoy, Safa; Perry, Allison K.; Kunze, Kyle N.; Singh, Harsh; Westrick, Jennifer C.; Chahla, Jorge
Abstract : Apophyseal avulsion fractures of the ischial tuberosity (AFIT) in pediatric athletes are relatively uncommon injuries with treatment and return to sport (RTS) outcomes being largely unknown. The purpose of this review is to perform a systematic review analyzing RTS and predictors of successful RTS for pediatric athletes sustaining AFIT. Studies reporting on athletes strictly under the age of 18 years sustaining an AFIT with reported RTS status were included. RTS was analyzed based on injury acuity, mechanism, and management, whereas the incidence of any complications was recorded. A total of 33 studies comprising 90 cases of AFIT were identified. The mean age of athletes sustaining injuries was 14.7 + 1.4 years (range, 9–17 years), most commonly participating in soccer ( n = 25), sprinting ( n = 21), and gymnastics ( n = 7). Acute trauma during sporting activities was responsible for 74.4% ( n = 77/90) of injuries. A total of 82% ( n = 74/90) of athletes reported successful RTS at an average of 7.0 + 5.0 months. Athletes undergoing surgery had a significantly higher RTS rate ( n = 36/38, 94.7%) compared with athletes treated nonoperatively (n = 38/52, 73.08%; P = 0.008). When reported, a high rate of misdiagnosis was reported (39.4%, n = 28/71). Complications were reported in 15.8% ( n = 7/38) and 32.7% ( n = 17/52) of athletes managed surgically and conservatively, respectively. As such, the high rate of misdiagnosis and subsequent high rate of complications and poor rate of RTS highlight the importance of accurate diagnosis and treatment. Future prospective studies evaluating patient outcomes based on fracture displacement, sporting activity, and management strategies are warranted to better treat pediatric athletes. Study design: Level IV, systematic review.